[Spichlerze przy ul. Chmielnej] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia spichlerze przy ul. Chmielnej nr 69-67, "Słoń", "Rothe Lau", "Biały Koń", ok. 1910 r.